ANALYSIS OF CONSUMER BEHAVIOUR TOWARDS THE USAGE OF MILK PRODUCTS IN SEKONDI-TAKORADI METROPOLIS, GHANA. - Twenefour, Frank B. K. (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The purpose of this paper was to find out the various variables that drive milk consumers to choose some brands and types of milk often consumed. It also sought to find out the level of awareness and consumption of the various types of milk on the market. Milk consumption in the SekondiTakoradi Metropolis is on the rise, and this is a good indication since milk is rich in many nutrients which help in fighting against malnutrition. Milk products provide a lot of nutrients to all manner of people. However, milk also has some health challenges for its consumers largely due to the level of fat and cholesterol. There are different types of milk on the Ghanaian market and these are classified based on the level of fat they contain. The current investigation or research was executed using the method of complex statistics information. The study examined 686 respondents from the Sekondi-Takoradi Metropolis. Data was collected on 20 consumer attributes considered important when purchasing milk. Direct observation, a structured questionnaire and a face-to-face interview were used to collect the data which was analyzed using some statistical tools including binary logistic regression model. It was found that, most consumers consume full cream or high fat milk, and milk products which is a major threat to health conditions. Brand familiarity, taste, flavour, nutritional values and creamy nature of the product were cited as salient attributes driving consumers to patronize full cream milk. Also, there is a low level of awareness of the various types of milk on the market, especially the ones with low-fat content, hence consumers do not consider the fat content of milk products before buying. However, the study shows that when consumers are well educated about these types of milk products and their level of cholesterol or fat, they will be much sensitized to go in for milk and milk products with low-fat content rather than the products with high-fat content.